O conto "A casa de Astérion" e a seletividade do sistema penal brasileiro - Castro, Kleber Sato Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This study aimed to analyze the Brazilian penal system from the perspective of the Labeling Approach Theory. In a period when prisons in Brazil are in crisis, it is worth reflecting on the reasons and possible resolutions for the present situation, and to understanding how this context relates to penal selectivity. Furthermore, all this theoretical accumulation was compared with the short story “The house of Asterion’’; from the book The Aleph by Jorge Luis Borges. In this sense, some steps were taken in order to reach the current objective. As the analysis of historical aspects and the present context of the Brazilian penal system; the in-depth study on the Labeling Approach Theory and outsider behavior; and, finally, the application of this theory in the current situation of the penitentiary model in Brazil. Simultaneously, an essay was made on the chosen short story and an analogy of it with the main object of study was proposed. Therefore, bibliographic research was chosen as a method of data collection, through the elaboration of records about the central works present in the theoretical framework, and, later, the literature review of these records, in order to select the information that best related to the theme. From the data analysis it was possible to assess how selective is the current penal system in Brazil and how this contributes to the increase of criminality in the national territory. It is worth emphasizing that it has been demonstrated how important it is to revise Brazilian legislation that acts selectively, in addition to being crucial for a reform to improve the precarious conditions of prisons in Brazil. Finally, through the entire study carried out, it was possible to contribute to the updating and development of this theme, which is extremely relevant to the legal debate. In addition to making academic legal study more accessible to readers who do not have an affinity with this area.

Este estudo objetivou analisar o sistema penal brasileiro sob a perspectiva da teoria da rotulação social. Em um período em que as penitenciárias no Brasil se encontram em crise, é válida a reflexão acerca dos motivos e possíveis resoluções para a presente conjuntura, além do entendimento de como esse contexto se relaciona com a seletividade penal. Além disso, todo esse acúmulo teórico foi comparado com o conto “A casa de Astérion’’; da obra O Aleph de Jorge Luis Borges. Nesse sentido, algumas etapas foram percorridas a fim de que se alcançasse o atual objetivo. Como as análises dos aspectos históricos e do presente contexto do sistema penal brasileiro; o estudo aprofundado sobre teoria da rotulação social e acerca do comportamento desviante; e, finalmente, a aplicação dessa teoria na atual situação do modelo penitenciário do Brasil. Simultaneamente, foi feito um ensaio sobre a obra escolhida e proposta uma analogia dela com o objeto principal de estudo. Para tanto, a pesquisa bibliográfica foi escolhida como método de coleta de dados, através da elaboração de fichamentos acerca das obras centrais presentes no referencial teórico, e, posteriormente, da revisão de literatura desses fichamentos, a fim de que se pudesse selecionar as informações que melhor se relacionavam com o tema. A partir da análise de dados foi possível avaliar o quão seletivo é o atual sistema penal no Brasil e como isso contribui para o aumento da criminalidade em território nacional. Vale frisar que ficou demonstrado como é importante uma revisão da legislação brasileira que atua de forma seletiva, além de ser crucial uma reforma que melhore as condições precárias das penitenciárias no Brasil. Enfim, por meio de todo o estudo realizado foi possível contribuir para a atualização e desenvolvimento dessa temática que apresenta extrema relevância para o debate jurídico. Além de tornar mais acessível o estudo jurídico acadêmico para leitor que não possui afinidade com essa área.
The short story "The house of Asterion" and the selectivity of the brazilian penal system
Keywords: System; Criminal; Labeling; Approach; Selectivity; Sistema; Penal; Rotulação; Social; Seletividade